2018 Review of the Fund's Capacity Development Strategy. (Policy Papers; Policy Paper ;, 2018)
Capacity development (CD) is one of the Fund's three core activities and has grown in importance in recent years. It supports member countries' efforts to build the institutions and capacity necessary to formulate and implement sound economic policies, thereby complementing the Fund's surveillance and lending mandates. Member countries, partners, and external commentators give the Fund high marks for the quality of its CD. At the same time, efforts need to continue to strengthen Fund CD to serve members' current and evolving needs. The 2018 CD Strategy Review examines progress under the Fund's 2013 CD Strategy and proposes a CD strategy for the next five years. It notes substantial progress in addressing the 2013 recommendations, which included strengthening the CD governance structure, enhancing the prioritization processes, clarifying the funding model, strengthening monitoring and evaluation, promoting greater integration of TA and training, exploiting new technologies for delivery, and leveraging CD as outreach. However, background work for this review also pointed to the need to strengthen the CD framework further. The review builds upon the existing CD strategy, focusing on two mutually reinforcing objectives. First, the impact of Fund CD needs to be increased by further strengthening integration with the Fund's policy advice and lending operations, while continuing to make progress in framing CD through comprehensive strategies tailored to each member's needs, capacity, and conditions, focusing on implementation and outcomes. Stronger coordination between CD and the Fund's other core functions will better connect CD with countries' risks and vulnerabilities and ensure surveillance and lending integrate lessons from CD more effectively. Second, the efficiency of CD needs to be increased by improving CD processes and systems. This will enhance transparency and strengthen the basis for strategic decision making. Five specific areas of recommendations support the strategy. Likewise, they mitigate institutional risks stemming from the Fund's CD activities. They include clearer roles and responsibilities for key internal and external stakeholders in the CD process; continued strengthening of prioritization and monitoring; better tailoring and modernization of CD delivery with a focus on implementation of TA recommendations; greater internal consultation and sharing of CD information; and further progress in external coordination, communication, and dissemination of information (Annex I).